Learning environments and pedagogical model of an engineering design degree program - Gomes, António (2013)
This paper presents the theoretical background that supports the use of project-based learning (PBL) in engineering education and relates it to the pedagogical framework implemented in the new first cycle degree program Technology and Product Design offered by the University of Aveiro. The program structure is described focusing on the learning environments used in each course of this interdisciplinary program. The purpose of this paper is to characterize this new curriculum in order to contribute to the discussion about engineering education pedagogy with a complete program implementation experiment. Issues like courses architecture and scope, assessment, student/teacher ratios and group sizes are addressed. Furthermore, students’ perceptions of the learning environments is investigated and compared with their learning results. Ultimately the implications of a student-centred learning curriculum design, based on a PBL strategy, are discussed.